2022
DOI: 10.1007/s11886-022-01759-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Meteorological Factors and Air Pollutants on Acute Coronary Syndrome

Abstract: Purpose of Review Several studies have found that air pollution and climate change can have an impact on acute coronary syndromes (ACS), the leading cause of death worldwide. We synthesized the latest information about the impact of air pollution and climate change on ACS, the latest data about the pathophysiological mechanisms of meteorological factors and atmospheric pollutants on atherosclerotic disease, and an overall image of air pollution and coronary heart disease in the context of the COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…The presented results from our analysis correlate nitric oxide air pollution with chronic coronary syndrome, indicating progressive atherosclerotic plaque development. This novel finding broadens the scientific perspective on the pathophysiology of coronary culprit lesion and, in contrary to previous reports, suggests the relationship between meteorological factors and acute coronary syndrome risk [44,45]. More interestingly, Diaz-Chiron et al [46] presented the results of myocardial infarct size in relation to nitric oxide air and pollution and inflammatory activation measured by the neutrophil-to-lymphocyte ratio.…”
Section: Discussionmentioning
confidence: 75%
“…The presented results from our analysis correlate nitric oxide air pollution with chronic coronary syndrome, indicating progressive atherosclerotic plaque development. This novel finding broadens the scientific perspective on the pathophysiology of coronary culprit lesion and, in contrary to previous reports, suggests the relationship between meteorological factors and acute coronary syndrome risk [44,45]. More interestingly, Diaz-Chiron et al [46] presented the results of myocardial infarct size in relation to nitric oxide air and pollution and inflammatory activation measured by the neutrophil-to-lymphocyte ratio.…”
Section: Discussionmentioning
confidence: 75%
“…While the exact mechanisms remain not fully known and comprehended, various pathophysiological explanations have been proposed to elucidate why exposure to either cold or heat can trigger acute coronary disease. Exposure to both low and high temperatures has been associated with an augmentation in platelet and red cell counts, an elevation in fibrinogen concentration, and increased blood viscosity, ultimately leading to heightened thrombogenicity [ 12 , 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The physiopathological mechanism by which climate changes determine the increase in the number of AMI hospitalizations remains uncertain. It has been observed that exposure to low atmospheric temperatures causes an increase in the serum level of catecholamines, fibrinogen, and platelets, as well as an increase in blood pressure and heart rate [ 12 , 13 ]. In the context of global warming in recent years, the hot months seem to be associated more and more with the increase in the number of hospitalizations due to ACS [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[95][96][97] Driven by an interest in how associations with air pollution may change under climate change and reflecting differences in air pollution sources and components in different seasons, many studies have explored associations between various air pollutants and climatic components (eg, temperature [especially extremes], humidity) with a variety of cardiovascular outcomes. 98,99 In a time-series study in Hong Kong, the detrimental effects of air pollution on emergency IHD admissions were highest in the cool and dry season. 100 In another study in Lanzhou city, China, 101 the associations of air pollution with coronary heart disease hospitalizations were also greater during the cold season.…”
Section: Compendium On Environmental Impacts On Cardiovascular Health...mentioning
confidence: 99%